Recent Developments in Cellular Immunotherapy for HSCT-Associated Complications - Reis, Monica; Ogonek, Justyna; Qesari, Marsela; Borges, Nuno M.; Nicholson, Lindsay; Preußner, Liane; Dickinson, Anne Mary; Wang, Xiao-nong; Weissinger, Eva M.; Richter, Anne (Frontiers in Immunology, 2016)
Allogeneic HSCT is associated with serious complications and improvement of the overall clinical outcome of patients with hematological malignancies is necessary. During the last decades, post-transplant donor-derived adoptive cellular immunotherapeutic strategies have been progressively developed for the treatment of graft versus host disease (GvHD), infectious complications, and tumor relapses. To date, the common challenge of all these cell-based approaches is their implementation for clinical application. Establishing an appropriate manufacturing process, to guarantee safe and effective therapeutics with simultaneous consideration of economic requirements is one of the most critical hurdles. In this review we will discuss the recent scientific findings, clinical experiences, and technological advances for cell processing, towards the application of MSC as a therapy for treatment of severe GvHD, virus-specific T cells for targeting life-threating infections, and of CAR-engineered T cells to treat relapsed leukemia.